If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(p + -8) = 75 Reorder the terms: 5(-8 + p) = 75 (-8 * 5 + p * 5) = 75 (-40 + 5p) = 75 Solving -40 + 5p = 75 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '40' to each side of the equation. -40 + 40 + 5p = 75 + 40 Combine like terms: -40 + 40 = 0 0 + 5p = 75 + 40 5p = 75 + 40 Combine like terms: 75 + 40 = 115 5p = 115 Divide each side by '5'. p = 23 Simplifying p = 23
| x^3+2x^2=6 | | 15/x=100/160 | | 2x+122-77x=-2 | | 7(n-6)-4=-102 | | 2/x=8/28 | | 2(3a-7)=180 | | 14x-10x=24+36 | | 7(x-7)+12=4(x-7) | | 6x^2+8xy+8x=0 | | logx64=-3/-2 | | 7x-11=4x-3+5x | | 6n+12=-35-6n | | 0.1x-0.7(5-x)=-0.7 | | -(14-7p)=-49 | | -6x+3(x+5)=6 | | f(x)=(2x^6) | | 2w^2-3w-209=0 | | 6x+3(x+5)=6 | | 3x+27=5x-5 | | 10q^4/3r^4s^4/5pq^2/qr^3s | | 9x+5=14+6x | | 2pisquared= | | 2480/80 | | (8x^2-9)-(3x^2+5x+1)=equation | | (5x+8y)(4x-6y)= | | 6x+3=-37-2x | | 6x+3=37-2x | | 5x+9=27+2x | | 2x^2+8xy=0 | | 12.2+x-7.5=5.6 | | 10x=48-2x | | 5x-15=3x-15 |